2019
DOI: 10.1002/1878-0261.12554
|View full text |Cite
|
Sign up to set email alerts
|

FHR4‐based immunoconjugates direct complement‐dependent cytotoxicity and phagocytosis towards HER2‐positive cancer cells

Abstract: Directing selective complement activation towards tumour cells is an attractive strategy to promote their elimination. In the present work, we have generated heteromultimeric immunoconjugates that selectively activate the complement alternative pathway (AP) on tumour cells. We used the C4b‐binding protein C‐terminal‐α‐/β‐chain scaffold for multimerisation to generate heteromultimeric immunoconjugates displaying (a) a multivalent‐positive regulator of the AP, the human factor H‐related protein 4 (FHR4) with; (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…FHR proteins were shown to enhance complement activation and C3 deposition on surfaces, including altered host surfaces such as those of necrotic cells ( 35 37 , 40 , 48 , 57 ) and tumor cells ( 81 ), but also on microbes ( 33 , 82 , 83 ). Here, we showed that FHR-1 and FHR-5 enhance complement activation on necrotic cells via their interactions with mCRP and PTX3.…”
Section: Discussionmentioning
confidence: 99%
“…FHR proteins were shown to enhance complement activation and C3 deposition on surfaces, including altered host surfaces such as those of necrotic cells ( 35 37 , 40 , 48 , 57 ) and tumor cells ( 81 ), but also on microbes ( 33 , 82 , 83 ). Here, we showed that FHR-1 and FHR-5 enhance complement activation on necrotic cells via their interactions with mCRP and PTX3.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Hebecker and Józsi was the first to challenge the paradigm, demonstrating that, by binding C3b, FHR-4 in fact enhances alternative pathway activation ( 85 ), a mechanism which was also suggested previously by Närkiö-Mäkelä et al ( 96 ). This property of FHR-4 was recently exploited to overcome complement resistance of HER-2 positive tumor cells by applying FHR-4 based immunoconjugates ( 97 ). Studies by Tortajada et al and Goicoechea et al soon followed and described another mechanism, namely de-regulation by FHRs through competition with FH.…”
Section: Major Challengesmentioning
confidence: 99%
“…CFHR4 as a rst-line epileptic drug phenytoin hypersensitivity prognostic marker, the sensitivity is 16%, while the speci city is 97% [38]. The above results suggest that FHR4 plays a potential role in the disease occurrence and development and may represent a novel therapeutic molecule [19].…”
Section: Discussionmentioning
confidence: 99%
“…As an amphiphilic protein, CFHR4 exists in human plasma and triglyceride-rich lipoproteins in the monomer or dimer form [14,15] and can play a role as a component of lipoproteins [16]. CFHR4 consists of a short common repetitive sequence (SCR) domain, which binds Creactive protein through its N-terminal SCR, activates the classical complement pathway, regulates complement-mediated foreign antigen processing [17], and enhances the regulation of phagocytic microorganisms and damaged host cells [18][19][20]. Studies have shown that CFHR4 shows abnormalities in various diseases, which may be connected to disease incidence and progression.…”
Section: Introductionmentioning
confidence: 99%